Phytochemistry and antibacterial activity of Citrus sinensis extracts against three pathogenic bacteria in Benin - YOVO, Mahudro; ALITONOU, GUY ALAIN; SESSOU, PHILIPPE; DEDOME, Ludolphe; TCHOBO, Fidèle; AVLESSI, FÉLICIEN; MENUT, Chantal; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2016)
This work is a contribution to the phytochemical and biological studies of Citrus sinensis leaves' extracts in Benin. The main chemical groups and total phenols contents of non-volatiles extracts were investigated. Essential oil of Citrus sinensis was extracted and analyzed by gas chromatography coupled with mass spectrometry. The antimicrobial activity of various extracts was evaluated on Staphylococcus aureus, Escherichia coli and K. pneumoniae by disk diffusion method. The results obtained showed that the essential oil of Citrus sinensis leaves were mainly composed of hydrogenated monoterpens (74%) and oxygenated monoterpens (24%). The major compounds in this oil were sabinene (33.1%) and Delta-3-carene (14.9%). Aqueous and semi-ethanolic extracts of this plant were studied and contained anthocyanins, leucoanthocyanes, flavonoids, catechin tannins and saponins. The ethanol extract meanwhile contained leucoanthocyanins, gallic tannins catechin tannins and saponins. Phytochemical studies indicate that the phenolic contents of the non-volatiles extracts varied from 664.00 ± 8.80 to 921.69 ± 0.35 mg EAG / g MS, 31.08 ± 0.11 to 47.78 ± 5.60 mg EC/g MS and 16.98 ± 0.95 to 73.01 ± 2.49 mg EC/g MS respectively for total phenol, flavonoid and tannins. The non-volatiles extracts from C. sinensis exhibit no antibacterial activity on Staphylococcus aureus, Escherichia coli and Klebsiella pneumoniae in contrast to the essential oil that exhibited moderate activity on S. aureus and E coli.
Keywords: Citrus sinensis; S. aureus; Essential oil; antibacterial activity; pathogenic strains